Association of Endothelial Function with Parental Hypertension in Normotensive-Obese African-American Women: A Pilot Study. (3rd February 2019) - Bond, Vernon; Becknel, Karissa; Kumar, Krishna; Dorsey, James; Gorantla, Vasavi R.; Volkova, Yulia A.; Millis, Richard M.
Abstract : Obese African-American (AA) women are at high risk of hypertension (HT) and cardiovascular disease (CVD). Flow-mediated dilation (FMD) and arterial augmentation index (AI) are measures of endothelial function and arterial stiffness. Whether endothelial function and arterial stiffness predict risk of HT or CVD in obese African-American women with, versus without, parental histories of HT and whether aerobic exercise is an effective countermeasure remain unclear. The capacity for FMD is partly heritable. Therefore, we tested the hypotheses that less FMD and greater AI may be found in normotensive-obese, young-adult (18-26 year-old) AA women with hypertensive parents (n=10) than in a matched control group with normotensive parents (n=10) and that a single bout of aerobic exercise improves both endothelial function and arterial stiffness, with less improvement in the women with hypertensive parents. We studied each subject while at rest, 20 min before and 20 min after, 30 min of aerobic exercise. The exercise-induced changes and parental hypertension-related differences in AI were not significant. The exercise increased FMD in both of the groups with no significant difference in magnitude between the women with hypertensive and normotensive parents. FMD was significantly less in the women with hypertensive parents than in the women with normotensive parents after, but not before, the exercise (mean ±95% confidence interval of 11.3 ± 4.9% vs. 15.6 ± 4.9%, P=0.05). These findings suggest that a 30-min bout of aerobic exercise may improve FMD and unmask endothelial dysfunction in normotensive-obese, young-adult AA women with parental histories of HT. Future studies should determine whether regular aerobic exercise protects obese AA women from the endothelial dysfunction associated with diabetes and prevents CVD in this high-risk population.